FC070: Lumasiran for Patients with Primary Hyperoxaluria Type 1 with Impaired Kidney Function: Data from the 6-Month Analysis of the Phase 3 Illuminate-C Trial. (3rd May 2022) - Groothoff, Jaap; Michael, Mini; Shasha-Lavsky, Hadas; Lieske, John; Frishberg, Yaacov; Simkova, Eva; Sellier-Leclerc, Anne-Laure; Arnaud, Devresse; Guebre-Egziabher, Fitsum; Azime Bakkaloglu, Sevcan; Mourani, Chebl; Saqan, Rola; et al.
Abstract: BACKGROUND AND AIMS: Primary hyperoxaluria type 1 (PH1) is a rare genetic disorder characterised by hepatic oxalate overproduction that leads to progressive kidney disease. As kidney function declines, oxalate elimination is compromised and plasma oxalate (POx) increases, leading to systemic oxalosis. In chronic kidney disease (CKD) stages 3b–5, elevated POx is directly related to the pathophysiology of oxalosis, and reduction of POx is a relevant clinical trial endpoint. Lumasiran, an RNA interference therapeutic designed to reduce hepatic oxalate production, is indicated for the treatment of PH1 in all age groups. Data from the ILLUMINATE-C trial (EudraCT: 2019–0 013 346-17) demonstrated substantial reductions in POx and acceptable safety in patients with PH1 with impaired kidney function, including patients on haemodialysis (HD), who received lumasiran for 6 months. In Cohorts A (no HD) and B (on HD), respectively, lumasiran led to 33.33% [95% confidence interval (95% CI): −15.16 to 81.82] and 42.43% (95% CI: 34.15–50.71) least-squares (LS) mean reductions in POx from baseline to Month 6 (the primary endpoint). Here, we present METHOD: ILLUMINATE-C is an ongoing Phase 3, single-arm study with two cohorts, Cohort A ( N = 6; no HD at study start) and Cohort B ( N = 15; on HD). The 6-month primary analysis period is followed by an extension period (EP) of up to 54 months. Key inclusion criteria include genetically confirmed PH1, eGFR ≤ 45 mL/min/1.73 m 2 and POx ≥ 20 μmol/L. Patients received weight-based dosing of subcutaneous lumasiran. Outcomes of interest for the current analysis included assessments of cardiac oxalosis using echocardiography, medullary nephrocalcinosis by kidney ultrasound, kidney stone events and burdensome symptoms of PH1. RESULTS: All 21 patients [43% female; 76% white; median age 8 (range 0–59) years] completed the 6-month primary analysis period. Among patients with abnormal left ventricular ejection fraction (LVEF; abnormal defined as LVEF < 55%) at baseline, 1/1 patient in Cohort A and 2/4 patients in Cohort B showed ≥ 5% improvement at Month 6. Among patients with abnormal global longitudinal strain (GLS, a measure of LV contractility more sensitive than LVEF for predicting outcomes; abnormal defined as |GLS| <15%) at baseline, 1/1 patient in Cohort A and 3/3 patients in Cohort B showed ≥ 2% improvement at Month 6. In Cohort A, 5/6 patients had nephrocalcinosis at baseline, 2 remained stable, none worsened, and 3 improved (2 unilateral and 1 bilateral improvement) at Month 6. In Cohort A, 1 patient did not have nephrocalcinosis at baseline and had bilateral worsening at Month 6. In Cohort B, 2/11 patients had nephrocalcinosis at baseline; both improved (1 unilateral and 1 bilateral improvement). In Cohort A, the rate of kidney stone events per person-year was 3.20 (95% CI: 1.96–5.22) in the 12 months prior to consent and 1.48 (95% CI: 0.55–3.92) during the first 6 months of lumasiran treatment. For patients in both cohorts, the most burdensome symptoms at baseline, including fatigue, nausea/decreased appetite, bone pain and decreased mobility, improved or remained stable at Month 6; none of the symptoms worsened. CONCLUSION: Lumasiran treatment resulted in substantial reductions in POx in patients of all ages with PH1 and advanced kidney disease. The observations regarding cardiac measures that reflect systemic oxalosis, together with the kidney stone event and nephrocalcinosis results, are consistent with mobilisation of oxalate from systemic stores. Data on these long-term outcomes will continue to be collected and further evaluated in the EP. These results, along with previous reports from ILLUMINATE-A and ILLUMINATE-B, provide evidence supporting the effectiveness of lumasiran across the full spectrum of patients affected by PH1.